Impact of Organizational Culture on the Successful Implementation of Business Strategy in the Digital Era: Literature Review - Lathifah, Nur; Fasya, Muhamdad Danda Zafilla; Noviyanti, Indah (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
A strong organizational culture that is in line with business strategy is essential for successful strategy implementation, especially in today's dynamic digital world. This research was conducted using a qualitative method by looking at scientific publications in Indonesia from 2014 to 2024. One of the beneficial aspects of organizational culture found in the research is innovation orientation, openness to change, customer orientation, and open cooperation and communication. In addition, it was found that organizational culture affects every step in strategy implementation, from strategy formulation, communication, execution, to evaluation and control. To align culture with business strategy in the digital age, it is best to engage employees, strengthen leadership that supports change, implement an aligned reward system, use information technology, conduct regular cultural assessments, and design cultural development programs. Success in implementing strategies in the digital age that requires organizations to remain flexible, innovative, and responsive to change is key to aligning organizational culture with business strategy. This study enhances our understanding of the critical role of organizational culture in supporting business strategy execution in the digital age. It also helps us understand cultural alignment strategies and practices that businesses in Indonesia can implement.